Empowerment and human resource capacity building in Homestay Village Borobudur, Magelang - Lintang Muliawanti; Fadillah Sandy; Aning Az Zahra (Universitas Muhammadiyah Magelang, 2023)
This community service aims to enhance competency and skills in hospitality and housekeeping to improve the quality of homestay village services in Ngaran II hamlet. The implementation method involves several stages, namely socialization, training, and assistance in hospitality and housekeeping, as well as the establishment of a Tourism Information Center (TIC). The results of this program include fostering a spirit of improvement among homestay managers and enhancing the skills of homestay managers in hospitality and housekeeping.